Prognostic value of Serum Uric Acid in predicting Hospital mortality and morbidity in Patient with acute Coronary syndrome (Journal of Dhaka National Medical College & Hospital, 2017)
Background: Uric acid is an independent risk factor for cardiovascular disease. At present, Coronary artery disease (CAD) in one of the leading cause of death in the worldwide also in Bangladesh. Although studies were conducted abroad regarding association of scrum uric acid with in hospital out comes in patient with acute coronary syndrome. No data is yet available to show the association in our country.Objectives: The objective of the study was to assess the association of serum uric acid level on admission with in hospital outcomes of the patient, with acute coronary syndrome.Materials and Methods: This study was carried out in the department of cardiology, Dhaka National Medical Institute Hospital, Dhaka from October, 2014 to September 2015. In this case series study. 102 diagnosed Patients of acute coronary syndrome free from gout, renal disease, hepatic disorder and other malignant conditions were enrolled by non random sampling. Serum uric acid of all subject was measured within 24 hours of presentation. During hospital stay the outcome (good and bad) were observed in all subjects.Result: Patients with higher serum uric acid (SUA>6.5mg%, Group-II) were compared with patients with lower serum uric acid (SUA